Labour, Management and the Public - Goldenberg, H. Carl (Relations industrielles / Industrial Relations, 1964)
SummaryIn this paper, presented at the Fifth National Labour, Management Seminar, University of British Columbia, October 1963, the author expresses the fruits of his long experience as a mediator and an arbitrator in labour-management disputes. The parties must face the facts; the law cannot settle everything; a continuous bargaining system would prove valuable.